2007
DOI: 10.1186/1471-2164-8-60
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenomic analysis of the Actinomycetales mce operons

Abstract: Background: The genome of Mycobacterium tuberculosis harbors four copies of a cluster of genes termed mce operons. Despite extensive research that has demonstrated the importance of these operons on infection outcome, their physiological function remains obscure. Expanding databases of complete microbial genome sequences facilitate a comparative genomic approach that can provide valuable insight into the role of uncharacterized proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
259
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(268 citation statements)
references
References 95 publications
(115 reference statements)
9
259
0
Order By: Relevance
“…These two genes are intact in M. ulcerans ecovar Liflandii Lipoproteins. Lipoproteins in mycobacteria have been implicated in signal transduction (34) and evasion of mammalian cells (35), and some have a direct role in virulence as a part of transport systems (36). These proteins can be surface exposed and anchored by hydrophobic interactions, potentially to mycolic acids within the cell wall (37,52).…”
Section: Resultsmentioning
confidence: 99%
“…These two genes are intact in M. ulcerans ecovar Liflandii Lipoproteins. Lipoproteins in mycobacteria have been implicated in signal transduction (34) and evasion of mammalian cells (35), and some have a direct role in virulence as a part of transport systems (36). These proteins can be surface exposed and anchored by hydrophobic interactions, potentially to mycolic acids within the cell wall (37,52).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported previously that the vacJ mutant is less able than wild-type S. flexneri to escape the double membrane formed when the bacterium moves from one cell to another; about 50% of cells of the intracellular vacJ mutant were unable to escape the double membrane (26). Since it has been suggested that vacJ and vpsC are linked functionally (27), it is possible that the defect in cell-to-cell spread of the vpsC mutant can also be attributed to an inability to escape the doublemembrane vacuole.…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al (26) observed a similar phenotype for an S. flexneri vacJ mutant. While the S. flexneri vacJ gene is not part of the vps operon, it is predicted to be part of the Vps/VacJ ABC transporter system, since it is found in an operon with vps homologs in other bacteria (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although mce clusters, which have identical structures consisting of two yrbE genes (yrbEA and yrbEB), encoding integral membrane proteins, followed by six mce genes (mceA to mceF), encoding exported or membrane-tethered proteins, were first identified due to their critical role in bacterial invasion and survival in mammalian cells (55), not all bacteria possessing mce clusters are found as pathogens (such as Mycobacterium smegmatis and Streptomyces coelicolor). This indicates that the products of mce clusters have physiological functions other than acting as virulence factors, e.g., acting as novel ABC uptake transporters (56). This speculation was soon proved by showing that the Mce4 system of Rhodococcus jostii RHA1 functions as a steroid uptake transporter (34).…”
Section: Resultsmentioning
confidence: 95%